Cost and revenue overruns of the Olympic Games 2000-2018 - Preuß, H.; Andreff, V.; Weitzmann, M. (Event- und Impaktforschung, 2019)
In this open access book the cost and revenue overruns of Olympic Games from Sydney 2000 to PyeongChang 2018 from eight years before the Games to Games-time are investigated to provide a base for future host cities. The authors evaluated the development of expenditure and revenues of the organizing committees to operate the event, and the investment of taxpayers` money for Olympic venues (non-OCOG budget). The study is based on data collected worldwide and is currently the most advanced study on cost and revenue changes of Olympic Games.